PELATIHAN PENGELOLAAN PERPUSTAKAAN DESA SIMPANG DOLOK SEBAGAI SENTRA INFORMASI BERBASIS ISLAM - Hidayat, Rahmat; Thaib, Zamakhsyari bin Hasballah; Lubis, Muya Syaroh Iwanda (MAJU : Indonesian Journal of Community Empowerment, 2025)
Library management training is very important, especially in villages that can be said to be partially undeveloped. This village library aims to make the community, especially children, young people and adults, aware of the importance of literacy, as well as to educate the community. Not only limited to information and sources of knowledge for the community, this village library will also become an Islamic-based information center, where the community will learn a lot about Islamic teachings in this library. The problem that often arises in this case is that there are still people who cannot read and write, so it becomes difficult for the village to run this program then access to the library in the village is small and cannot accommodate many people. The method in this activity is training by conducting surveys, education and approaches to the community, the results obtained by the community are very enthusiastic about the activities carried out